Submerged fermentation of amylase enzyme by Aspergillus flavus using Cocos nucifera meal - Arunsasi, M; Kani, S Manthiri; Jegadeesh, G; Ravikumar, M (Kathmandu University Journal of Science, Engineering and Technology, 2010)
Soil samples were collected from the coastal region of Neendakara, along the West cost of Kerala, India. 15 fungal species were isolated and identified by using lacto phenol cotton blue staining method. From this, Aspergillus flavus was tested in Starch Hydrolysis Agar Medium for its amylase enzyme production under sumerged aerobic fermentation with different physico- chemical properties of substrates. Cocos nucifera meal was used as a carbon source. Heavy metals were added to these medium and were used as a modified medium. The effect of different carbon source, nitrogen compound and physico-chemical conditions like temperature, pH and incubation periods were studied for derivation of amylase enzyme. The molecular weight of enzyme was determined by SDS –PAGE. The role of heavy metals was determined by ion exchange chromatography. Cocos nucifera meal medium with dextrose has shown the highest amylase production at pH 6.0 and temperature of 30ºC with protein content of 201μg/ml; 98.4μg/ml and dry biomass of 1.28μg/ml. Keywords: Soil samples; A. flavus; amylase; SDS-PAGE; Ion exchange chromatography; submerged aerobic fermentation DOI: 10.3126/kuset.v6i2.4015 Kathmandu University Journal of Science, Engineering and Technology Vol.6. No II, November, 2010, pp.75-87